English for Software Engineering Students - Сердюкова, Ольга Іванівна (Національний технічний університет "Харківський політехнічний інститут", 2023)
This guide is for the students who are interested in Software Engineering. The guide considers topics relevant to their scientific interests.There are 6 units in the textbook. Each unit’s tasks consist in finding out a new information on diferent topics concerning speciality. Unit 1 gives an opportunity to the student to master important terminology in Software Engineering. Students should train the pronunciation of each word and memorize it before doing some exercises with the corresponding vocabulary. Reading expands the knowledge in the field and answers such necessary questions as what Software Engineering is, what importance of Software Engineering consists in, which solutions exist to overcome challenges in Software Engineering. Unit 2 has lots of Business English idioms and expressions; as well as everyday English vocabulary used throughout a Software Engineer’s day.The idioms and expressions are to be memorized and used in different situations. Unit 3 involves students in Software Engineering Interview. Accessories and peritherals are regarded when doing reading tasks of the unit. Unit 4. Students will be able to find out the answers to the following questions on Mechanical Engineering: What is mechanical engineering? What is the concern of mechanical engineering? What are the fields the mechanical engineering is involved in? What are the specializations a mechanical engineer works on? Unit 5. There are two major classifications of software, namely System Software and Application Software to be discussed. Unit 6. E-commerce is discussed by students after reading several texts and watching videos. The guide is provided by Software Engineering Vocabulary to be interpreted in English. The students can use it when it is necessary while studying either this or that topic. Good luck to you, dear students!
Keywords: methodical instructions; english; engineering students; software engineering; software engineering; e-commerce